Lianas in gaps reduce carbon accumulation in a tropical forest - Schnitzer, Stefan A.; van der Heijden, Geertje; Mascaro, Joseph; Carson, Walter P. (Ecological Society of America, 2014)
Treefall gaps are the “engines of regeneration” in tropical forests and are loci of high tree recruitment, growth, and carbon accumulation. Gaps, however, are also sites of intense competition between lianas and trees, whereby lianas can dramatically reduce tree carbon uptake and accumulation. Because lianas have relatively low biomass, they may displace far more biomass than they contribute, a hypothesis that has never been tested with the appropriate experiments. We tested this hypothesis with an 8-yr liana removal experiment in central Panama. After 8 years, mean tree biomass accumulation was 180% greater in liana-free treefall gaps compared to control gaps. Lianas themselves contributed only 24% of the tree biomass accumulation they displaced. Scaling to the forest level revealed that lianas in gaps reduced net forest woody biomass accumulation by 8.9% to nearly 18%. Consequently, lianas reduce whole-forest carbon uptake despite their relatively low biomass. This is the first study to demonstrate experimentally that plant–plant competition can result in ecosystem-wide losses in forest carbon, and it has critical implications for recently observed increases in liana density and biomass on tropical forest carbon dynamics.